A new species of Agrilozodes Théry, 1927, new record for A. pygmaeus (Kerremans, 1897) and a key for the genus (Coleoptera, Buprestidae) - Portela, Clayton; Mermudes, José Ricardo M. (Zootaxa, 2013)
Agrilozodes bellamyi sp. nov. from the Caatinga Biome (type locality: Juazeirinho, Paraíba, Brazil) is described and illus-trated. It differs from the other five known species mainly by the moderate longitudinal elevation between the eyes, pos-terolateral angles of pronotum acute and oblique, mesoepisternum excavated, elytral color pattern and elevation of interestriae 2 and 4. The distribution of A. pygmaeus is extended to Rio de Janeiro, Brazil. Photographs of six species as well as a key to the six species of the genus are provided.